Determinants of Brand Loyalty in Health Sector of Pakistan - Malik, Fozia; ., Omer Malik (Information Management and Business Review, 2012)
The purpose of this paper is to investigate the determinants of brand loyalty in health sector of Pakistan, the main theme is to study the relationship between dependent variable that is brand loyalty and determinants of brand loyalty i.e. independent variables that are brand knowledge, brand social responsibility image, service involvement and perceived service quality. Data was collected through questionnaire from customers of the health sector industry in twin cities of Islamabad and Rawalpindi. Out of 200 questionnaires 175 questionnaires received back in which 160 were properly filled which shows 80% response rate that is highly positive response. The results show that the independent variables have significant impact on dependent variable (brand loyalty). We have limited our research to the health sector of the twin cities i.e. Islamabad and Rawalpindi only, rather than the entire health industry of Pakistan. Research related to in depth analysis of the topic can be further done in different multiple dimensions. One can include much more complex demographics portion in the study in order to find out for example the impact of gender on the variable of brand loyalty.